A small-scale 'Development Impact Bond' for hepatitis C diagnosis and treatment financing in Cameroon: the way to elimination? - Charlotte Michèle Dieteren; Alexander Christiaan Boers; Tatiana Mossus; Frida Essomba; Guy Wafeu; Berthe Agnouanang; William Thomas; Oudou Njoya; Roel Arnold Coutihno (Journal of Global Health Reports)
# Background